Efficacy and Safety of Dapagliflozin in Type 2 Diabetes According to Baseline Blood Pressure: Observations From DECLARE-TIMI 58 Trial. Issue 21 (5th May 2022) - Furtado, Remo H.M.; Raz, Itamar; Goodrich, Erica L.; Murphy, Sabina A.; Bhatt, Deepak L.; Leiter, Lawrence A.; McGuire, Darren K.; Wilding, John P.H.; Aylward, Philip; Dalby, Anthony J; Dellborg, Mikael; Dimulescu, Doina; et al.
Abstract : Background: Dapagliflozin improved heart failure and kidney outcomes in patients with type 2 diabetes (T2DM) with or at high risk for atherosclerotic cardiovascular disease in the DECLARE-TIMI 58 trial (Dapagliflozin Effect on Cardiovascular Events – Thrombolysis in Myocardial Infarction 58). Here, the aim was to analyze the efficacy and safety of dapagliflozin stratified according to baseline systolic blood pressure (SBP). Methods: The DECLARE-TIMI 58 trial randomly assigned patients with T2DM and either previous atherosclerotic cardiovascular disease or atherosclerotic cardiovascular disease risk factors to dapagliflozin or placebo. Patients were categorized by baseline SBP levels: <120, 120 to 129, 130 to 139, 140 to 159, and ≥160 mm Hg (normal, elevated, stage 1, stage 2, and severe hypertension, respectively). Efficacy outcomes of interest were hospitalization for heart failure and a renal-specific composite outcome (sustained decrease in estimated glomerular filtration rate by 40%, progression to end-stage renal disease, or renal death). Safety outcomes included symptoms of volume depletion, lower extremity amputations, and acute kidney injury. Results: The trial comprised 17 160 patients; mean age, 64.0±6.8 years; 37.4% women; median duration of T2DM, 11 years; 40.6% with prevalent cardiovascular disease. Overall, dapagliflozin reduced SBP by 2.4 mm Hg (95% CI, 1.9–2.9; P <0.0001) compared with placebo at 48 months. The beneficial effects of dapagliflozin on hospitalization for heart failure and renal outcomes were consistent across all baseline SBP categories, with no evidence of modification of treatment effect ( P interactions =0.28 and 0.52, respectively). Among normotensive patients, the hazard ratios were 0.66 (95% CI, 0.42–1.05) and 0.39 (95% CI, 0.19–0.78), respectively, for hospitalization for heart failure and the renal-specific outcome. Events of volume depletion, amputation, and acute kidney injury did not differ with dapagliflozin overall or within any baseline SBP group. Conclusions: In patients with T2DM with or at high atherosclerotic cardiovascular disease risk, dapagliflozin reduced risk for hospitalization for heart failure and renal outcomes regardless of baseline SBP, with no difference in adverse events of interest at any level of baseline SBP. These results indicate that dapagliflozin provides cardiorenal benefits in patients with T2DM at high atherosclerotic cardiovascular disease risk independent of baseline blood pressure. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01730534.